A Middle Miocene ( 14 Ma) vertebrate assemblage from Palasava, Rapar Taluka, Kutch (Kachchh) District, Gujarat State, western India. (4th May 2021) - Kapur, Vivesh V; Pickford, Martin; Chauhan, Gaurav; Thakkar, M.G.
ABSTRACT: The present article aims to record a recently discovered middle Miocene vertebrate assemblage (including marine and terrestrial mammals) from Palasava, Kutch (Kachchh) District, Gujarat State, western India. The faunal assemblage comprising fishes, chelonians, crocodiles, snakes, birds and mammals is significant in terms of palaeoecology, palaeoenvironment and biostratigraphy of the region and yields evidence concerning its biogeographic affinities linked to Neogene Eustatic history. Palasava fauna together with previously known Neogene (particularly Miocene) vertebrate assemblages from the Kutch region indicates the presence of a riverine-estuarine system(s) linked to the sea, i.e. the depositional centres were quite close to the sea. Furthermore, the Palasava vertebrate assemblage (recorded herein) points towards a prevalence of warm, humid/wet, tropical to sub-tropical environmental conditions. The terrestrial mammalian assemblage from Palasava represents at least seven families with six of the terrestrial mammalian taxa identified herein to the genus level, namely: Sanitherium, Sivameryx, Brachypotherium, Zygolophodon, Gomphotherium, and Deinotherium . The overall assemblage (including Zygolophodon and Deinotherium ) is indicative of a Middle Miocene, 14 ± 2 Ma (Langhian to Serravallian) age for the sedimentary succession at Palasava. Furthermore, a 14 Ma age for the Palasava fauna indicates a correlation to regression cycle R5 in the Tagus Valley succession of Portugal.